Assessment of water quality of Batang Rajang at Pelagus Area, Sarawak, Malaysia - Ling, Teck-Yee; Soo, Chen-Lin; Phan, Tze-Pei; Lee, Nyanti; Sim, Siong-Fong; Jongkar Grinang, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study was carried out to examine the water quality of Batang Rajang at Pelagus area, Sarawak, Malaysia. Water quality was determined at 12 stations along Batang Rajang and its tributaries in terms of in-situ and ex-situ water quality parameters. The results showed that most stations at main river were categorized as slightly polluted while most tributaries were clean according to the Water Quality Index. The river is suffering from organic pollution where almost all stations along the river contained high chemical oxygen demand (≈ 43.1 mg/L) and total ammonia nitrogen (≈ 0.520 mg/L) and were classified as Class III and IV at most of the stations. High suspended solids (218.3 mg/L) and low dissolved oxygen (4.6 mg/L) were observed at the main river. The low dissolved oxygen content from the Bakun dam upstream of the study area has an impact on the river particularly during dry season where DO dropped below the minimum required for sensitive aquatic organisms. As seven tributaries are within Class II indicating healthy freshwater ecosystems, they should be conserved as habitats for sensitive aquatic organisms. Conversely, proper management need to be initiated in particular, Sungai Merit tributary and the main river where DO were below the minimum required for sensitive aquatic organisms.